Расширение оптимизационной модели межотраслевого баланса для учета движения основных фондов и трудовых ресурсов - Лавров, Л.Г.; Карпец, Э.П. (Теорія оптимальних рішень, 2006)
A technique for development of the extended model of inter-branch balance with inclusion balances of capital assets and manpower resources in it’s composition. This approach is a technique basis for calculation and forecasting of the coefficients of capital assets-output and labour-output ratios.